Low and high body mass index values are associated with female nocturia. Issue 8 (23rd July 2019) - Ito, Hideaki; Aoki, Yoshitaka; Oe, Hideki; Taga, Minekatsu; Tsuchiyama, Katsuki; Yokoyama, Osamu
Abstract: Aims: We evaluated the relationship between body mass index (BMI), including low BMI, and nocturia in Japanese women. Methods: We collected data on 18 952 women who participated in a multiphasic health screening in Fukui, Japan, in 2006. The participants were asked to report any current or previous disease. Self‐reported current body weight and height were used to calculate the BMI. We analyzed the relationship between nocturia, as assessed by a questionnaire, and other variables including age, BMI, and comorbidities. Results: The participants' mean age was 60.6 years. Overall, the prevalence of nocturia (two or more voids/night) was 4.3% and increased in an age‐dependent manner. BMI did not affect nocturia in the young participants. The prevalence of nocturia was higher in the high‐BMI women (>25.0 kg/m 2 ) in their fifth and sixth decades, but the prevalence was higher in the low‐BMI (<18.5 kg/m 2 ) in the women more than 80‐years old. A multivariate analysis revealed a significant association between nocturia and the following: age, BMI, sleep disturbance, arteriosclerosis, cerebrovascular disease, chronic pulmonary disease, diabetes mellitus, and hypertension. Not only high BMI (which is already reported as a risk of nocturia) but also low BMI was a factor related to nocturia. Conclusion: Our findings indicate that in addition to obesity, low BMI is a factor of nocturia in women.